Question 1: Solve the factored quadratic equation (19x−3)(9+x)=0
To solve the equation, we can set each factor equal to zero:
-
\(19x - 3 = 0\)
- \(19x = 3\)
- \(x = \frac{3}{19}\)
-
\(9 + x = 0\)
- \(x = -9\)
Thus, the solution set is: \[ { -9, \frac{3}{19} } \]
Question 2: Which of the following quadratic equations is not solvable by grouping?
We can analyze how to factor each equation:
-
\(2x^2 - 2x - 10 = 0\)
- Can be factored as \(2(x^2 - x - 5) = 0\).
-
\(x^2 - 12x + 35 = 0\)
- Can be factored as \((x - 5)(x - 7) = 0\).
-
\(2x^2 + 14x + 12 = 0\)
- Can be factored as \(2(x^2 + 7x + 6) = 0\) and further as \(2(x + 6)(x + 1) = 0\).
-
\(x^2 - 2x + 1 = 0\)
- Can be factored as \((x - 1)(x - 1) = 0\) or \((x - 1)^2 = 0\).
The equation that is not solvable by grouping is: \[ 2x^2 - 2x - 10 = 0 \] as it requires a different factoring approach.
Question 3: Factor the expression \(49x^4 - 4y^6\)
This expression is a difference of squares, which can be factored using the formula \(a^2 - b^2 = (a - b)(a + b)\).
- \(a^2 = (7x^2)^2\) and \(b^2 = (2y^3)^2\)
Thus, we can rewrite it as: \[ 49x^4 - 4y^6 = (7x^2 - 2y^3)(7x^2 + 2y^3) \]
So the factored expression is: \[ (7x^2 - 2y^3)(7x^2 + 2y^3) \]
To fill in the blank spaces:
- First blank: \(x^2\)
- Second blank: \(y^3\)
Final factorization: \[ (7 , x^2 - 2y^3)(7 , x^2 + 2y^3) \]